2008
DOI: 10.1017/s000711450813361x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregation, eicosanoid production and thrombogenic ratio in individuals at high cardiovascular risk consuming meat enriched in walnut paste. A crossover, placebo-controlled study

Abstract: Walnut consumption produces beneficial cardiovascular effects. The aim of the present study is to compare the effects of meat enriched in walnut paste (WM) and low-fat meat (LM) consumptions on platelet aggregation, plasma thromboxane A 2 (TXA 2 , measured as TXB 2 ), prostacyclin I 2 (PGI 2 , as 6-keto-PGF 1a ) and the thrombogenic ratio (TXB 2 /6-keto-PGF 1a ) in volunteers at high CVD risk. Twenty-two adults were placed on a random, non-blinded crossover study involving two test periods (five portions WM/we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…To the best of our knowledge, there have been very few studies [28][29][30], other than those of our group [22], on n-3-enriched meat-products on eicosanoids and blood coagulation factors.…”
Section: Discussionmentioning
confidence: 85%
“…To the best of our knowledge, there have been very few studies [28][29][30], other than those of our group [22], on n-3-enriched meat-products on eicosanoids and blood coagulation factors.…”
Section: Discussionmentioning
confidence: 85%
“…Our group found that walnut paste-enriched meat improved the antioxidant status of individuals at increased CHD risk (Canales et al, , 2009Nus et al, 2007). The walnut paste-enriched meat lowered platelet aggregation and thromboxane B 2 levels, and the thromboxane B 2 /prostacyclin (6-keto-PF 1a ) ratio to a greater degree than low fat meat (LM) (Canales et al, 2009). Moreover, thrombogenic index values varied due to interaction between consumption of walnut paste-enriched meat and LM and apolipoprotein A4 (APOA4) 360 gene polymorphisms (Canales et al, 2010), and variations in antioxidant enzyme concentrations and PON-1 gene polymorphism levels were also detected (Jiménez-Colmenero et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…Study participants were strongly requested not to include any other meats or meat derivatives in their diet during the trials. Basal anthropometrical characteristics of the volunteers have previously been published (Canales et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested to reduce meat-products consumption on account of epidemiological evidences linking meat consumption with increased prevalence of degenerative diseases [16]. However, several studies have shown the benefits of frequent consumption of meat and optimized meat and meat-products in different populations [10,30,31]. Our group has demonstrated that the consumption of pâtés and frankfurters with optimized fat content decreased waist circumference, body fat mass and the waist/hip ratio in male at increased risk volunteers [15] and improved cholesterol transported by low density lipoproteins (LDLc) and lipoprotein ratios in a sample of male and female volunteers [17].…”
Section: Introductionmentioning
confidence: 99%